The Influence of Debtor’s Satisfaction Toward Cross-Selling Readiness and Providing Recommendations - Saraswati, Henny; Achsani, Noer Azam; Kirbrandoko, Kirbrandoko (UI Scholars Hub, 2015)
The achievement of the banking sector's lending product is not consistently followed by the same level of achievement of other products. Therefore, it is important to observe customer segmentation, figuring out customer satisfaction, and to find out the influence of customer satisfaction toward the customer's willingness to cross-sell and providing recommendations on each segmentation. The purpose of this research paper is to identify individual debtor segment, identifying the influence of debtor's satisfaction toward cross-selling willingness and providing recommendations, as well as to become a business strategy reference for companies. We investigate the service quality (reliability, responsiveness, assurance, empathy, and tangible) to observe the level of both satisfaction and loyalty of the debtors. The research is conducted with 93 respondents. The analytical method that is applied in this research paper is descriptive statistics, cross tabulation, and regression analysis. The research results indicate that the biggest number of debtors is on the low-interest loan segment on service and trade businesses, while for the medium-interest loan and high-interest loan the biggest number is on the trade businesses. In general, each segmentation is willing to cross-sell. However, the high-interest loan segment is more willing to cross-sell. On both low-interest loan and medium-interest loan segments, the debtors are willing to recommend the company's products to their relations. However, the debtors on the high-interest loan tend to be unwilling to do so. The results of this research also clarifies the theory that debtor's satisfaction has a significant relation with the willingness to cross-sell and providing recommendations (customer's loyalty). This may also help managers to provide a proper service for different debtor's segmentation.